2016
DOI: 10.17113/ftb.54.03.16.4143
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Lactobacillus reuteri from Spontaneous Sourdough as a Starter Additive for Improving Quality Parameters of Bread

Abstract: SummaryRetardation of microbial spoilage of bread can be achieved by the use of spontaneous sourdough with an antimicrobial activity. This study was undertaken to identify lactic acid bacteria naturally occurring in spontaneous sourdough and use them for quality improvement and prolonging shelf life of rye, wheat and rye with wheat bread. Identifi cation of isolates from spontaneous sourdough by pyrosequencing assay showed that Lactobacillus reuteri were dominant lactic acid bacteria. The isolates showed a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…These values are in excellent agreement with those of the present study regarding yeast leavened bread. Jonkuvienė et al [ 29 ] identified LAB naturally occurring in spontaneous sourdough and used them for quality improvement and prolonging the shelf life of rye, wheat + rye, and wheat bread. The identification of isolates from spontaneous sourdough by the pyrosequencing assay showed that Lactobacillus reuteri was the dominant lactic acid bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…These values are in excellent agreement with those of the present study regarding yeast leavened bread. Jonkuvienė et al [ 29 ] identified LAB naturally occurring in spontaneous sourdough and used them for quality improvement and prolonging the shelf life of rye, wheat + rye, and wheat bread. The identification of isolates from spontaneous sourdough by the pyrosequencing assay showed that Lactobacillus reuteri was the dominant lactic acid bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are used as starter cultures in food processing to induce changes in their properties such as texture modification, aroma, nutritional improvement , or food preservation. The main applications are as lactic starters in dairy and bakery products , but also in alcoholic drinks . In tannery, LAB could be use to achieve the required lowering pH by lactic acid fermentation, under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal capability of postbiotics was investigated in bread by spraying postbiotics on the surfaces of bread loaves. The postbiotics from Lactobacillus reuteri prevented the mold contamination for 15 days stored at 25 °C and improved the texture of the bread (Jonkuviene, Vaiciulyte‐Funk, Salomskiene, Alencikiene, & Miezeliene, 2016). The ability of postbiotics from an antifungal‐producing Lactobacillus to act on aflatoxin producer Aspergillus in wheat grains was investigated (Shehata, Badr, El Sohaimy, Asker, & Awad, 2019).…”
Section: Food Applications Of Postbioticsmentioning
confidence: 99%